STUDY OF JOINT ROUGHNESS AFFECTED ON SHEAR STRENGTH OF JOINT ROCK - Harianto, Henry
Shear strength for jointed rock is influenced by several parameters, including basic friction angle (?b) atau residual friction angle (?r), Joint Compressive Strength (JCS) dan Joint Roughness Coefficient (JRC). In determining the JRC value, there are 3 method that can be used, the first is using back calculation through tilt test, with a joint roughness profiles table, then by measuring the asperity amplitude. In this experiment, it has 10 samples (A-J) with different joint. From the laboratory test the JRC value will be calculated using 3 method, it will get 3 curved rock joint shear strength curves based on the Barton criteria in each sample. The condition of the sample was declared unweathered. From the test, it was found that sample A (the most smooth joint) had similiar 3 shear strength curves of joint rocks, in B-D (smooth-medium joint) samples, there were 2 shear strength curves coinciding (from the JRC value from back calculation through tilt test and the value of JRC from the joint roughness profile table). But in the E-J samples, three curves generated from each sample already have a significant difference. Therefore the calculation of JRC values by tilt test is recommended at a roughness of less than 8. For JRC values greater than 8 are recommended by using push test or shear-box test.